STRATEGI LIRANG DALAM PENENTUAN HARGA JUAL PISANG DI PASAR TRADISIONAL BLITAR - Endah Masrunik; Bambang Septiawan; Anditya Dian Hendriawan (Universitas Islam Balitar, 2019)
This study focuses to determine how the strategy in determining the selling price of bananas applied by banana traders in Blitar traditional markets. This study uses a qualitative research method with the approach of study phenomenology, by conducting in-depth interviews and observations related to the behavior and attitudes of traders in making a sale and purchase transaction. The results of this study shows that traders determine the selling price of bananas based on the lirang strategy, while in one part and will be divided into several lirang. Then it will see the type, size, a number of bananas in one lirang, level of ripe, and current market conditions. Determination of selling prices based on this lirang is considered easier by traders, because traders do not need to weigh the bananas they sell and this strategy or method has long been used by banana traders in traditional markets